EMPLOYEE PAYMENT INFORMATION SYSTEM DESIGN IN CV. RAMAYANA MARIHAT BUTAR - Sanjaya Pinem; Desy Rinika Purba (INFOKUM, 2018)
Employee payroll process on CV. So far, Ramayana is still done manually, with a process that is still manual, calculation errors cannot be avoided. This results in discomfort for employees at work, which in turn can reduce the productivity of the employees themselves. With these problems, the author makes a programming application that can facilitate the work of the CV administration section. Ramayana in managing employee attendance data which is the basis for calculating salaries, so that in the end an effective and efficient payroll system is obtained. CV payroll system. Ramayana is made web-based and MySQL, as the database.